2013
DOI: 10.1016/j.jhydrol.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Significance of floods in metal dynamics and export in a small agricultural catchment

Abstract: International audienceHigh-resolution monitoring of water discharge and water sampling were performed between early October 2006 and late September 2007 in the Montoussé River, a permanent stream draining an experimental agricultural catchment in Gascogne region (SW France). Dissolved and particulate concentrations of major elements and trace metals (i.e. Al, Fe, Mn, As, Cd, Cr, Cu, Ni, Pb, Sc and Zn) were examined. Our results showed that contamination levels were deficient to moderate, as a result of sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…However, the same correlation was not observed for Mn, Cd, and Zn. This behavior was also observed by Roussiez et al (2013) who showed that particulate metals (except for Cd and Mn) usually depict a strong correlation with Fe. Not surprisingly, neither the bedload nor the bedload/suspended sediment ratio was correlated with the metal concentration in this fraction.…”
Section: Correlating Hydrology and Metals Concentrationsupporting
confidence: 77%
“…However, the same correlation was not observed for Mn, Cd, and Zn. This behavior was also observed by Roussiez et al (2013) who showed that particulate metals (except for Cd and Mn) usually depict a strong correlation with Fe. Not surprisingly, neither the bedload nor the bedload/suspended sediment ratio was correlated with the metal concentration in this fraction.…”
Section: Correlating Hydrology and Metals Concentrationsupporting
confidence: 77%
“…5 shows the results of metal enrichment factors (EFs) for all locations considered in the two years. There is no general consensus concerning threshold of natural variability but some authors (Hernandez et al, 2003;Roussiez et al, 2013) have suggested that EF N 2 is indicative of a probable anthropogenic influence. Taking this threshold as a reference, it can clearly be seen from these plots that median EF values of Pb (b 1.2) and Mn (b0.9) are below this limit.…”
Section: Spearman's Correlation and Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Variations in water and sediment physicochemical conditions could therefore play an important role in their mobilisation in the dissolved phase, where they become more bioavailable and disclose toxic chemical forms (Eggleton and Thomas, 2004;Roussiez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The SPM-bound Cu was found to be isotopically lighter compared to the dissolved Cu, which may be related to isotopically heavier Cu associated with DOM in the dissolved phase (El Azzi et al, 2013;Vance et al, 2008). However, the distribution of Cu in particle-size fractions (i.e., sand, silt, clay) can also influence Cu mobilization from the soil during rainfall-runoff events (Roussiez et al, 2013;Wang et al, 2014). Cu can accumulate in the coarse particulate SOM (Besnard et al, 2001;Parat et al, 2002) as well as in finer soil particles that are preferentially mobilized by runoff (Di Stefano and Ferro, 2002).…”
Section: Introductionmentioning
confidence: 96%